Effect of Feeding Agaricus Bisporus (White Button) Mushroom on Serum and Liver Cholesterol and Excretion of Cholesterol and Bile Acids in Rats - Goyal, R.; Grewal, R. B. (Journal of Scientific Research, 2024)
This study investigated the hypocholesterolic effects of (Agaricus bisporus) an Indian edible mushroom, in male Albino rats. The study revealed a significant reduction in serum total cholesterol content in experimental groups I and II, fed with 5 and 10% mushroom diet, respectively. The decrease in cholesterol was attributed to a reduction in low-density lipoprotein (LDL) and very low-density lipoprotein (VLDL). No significant changes were observed in the concentration of serum high-density lipoproteins (HDLs) between the control and experimental groups. However, a significant increase was noted when HDL cholesterol was expressed as a percentage of total cholesterol. Liver cholesterol levels (total, LDL, and VLDL) were significantly reduced in the experimental groups compared to the control group. The liver HDL cholesterol content in the experimental groups I and II increased by 13 % and 28 %, respectively. Additionally, there was a significant increase in the bulk of faces produced by the experimental groups compared to the control group. Fecal excretion of cholesterol and bile acids also increased in rats fed a mushroom diet. Present findings suggest a potential hypocholesterolemic effect of Agaricus bisporus, highlighting its possible role in promoting cardiovascular health.